Pengaruh Citra Band Koes Plus Terhadap Loyalitas Penggemar Di Bandung Koes Plus Community - Sumirat, Pepen (Magister of Communication Science, Sahid University Jakarta., 2022)
Koes Plus was founded in 1969, previously known as Koes Brothers, is a band whose songs are often heard. Even though it is classified as â€œold schoolâ€, its existence is still felt by looking at the loyalty of fans from the young to the elderly. It can be proven by the establishment of successor bands to the formed community. Also the songs have been re-sung by today's singers. Koes Plus proves that it can maintain its image until now. The purpose of this study was to measure the influence of the image of the Koes Plus band on fan loyalty in Bandung Koes Plus Community in 2019.This study uses a quantitative approach, survey method with simple random sampling technique in 95 respondents as a sample. SPSS 25.0 is software used in data analysis techniques. The results of this study prove that there is a significant positive effect of Koes Plus Band Image on Fan Loyalty in Bandung Koes Plus Community (BKPC) by 51% (Coefficient of Determination)